Progress in seismology: turning data into evidence about the earth's interior - Miyake, Teru (Routledge, 2023)
This chapter gives an account of progress in seismology between 1889 and 1940. I argue that the difficulty of seismology is that seismic wave recordings are extremely information-rich but extremely complex, and progress in seismology during this period was the result of advances in methods for extracting information from complexly structured data. In particular, I divide the rough half-century in question into three periods. In the first period, seismological research focused on the question of whether the waves that are recorded by seismographs are correctly theoretically characterized. In the second period, the research focused on accounting for anomalies in the seismic wave recordings by finding an interpretation for each significant anomaly. In the third period, the research focus was on making inferences from interpreted seismic wave recordings to features of the earth’s interior. In particular, I draw a contrast between British and German seismology, showing that progress in British seismology was stifled by the lack of methods for properly interpreting seismic wave recordings.